Solvent encephalopathy. Issue 6292 (5th September 1981) - King, M D; Day, R E; Oliver, J S; Lush, M; Watson, J M
Abstract : Nineteen children aged 8-14 years were admitted over a six-year period with an acute encephalopathy due to toluene intoxication. Seven had a history of euphoria and hallucinations. The remainder presented with coma (4), ataxia (3), convulsions (3), and behaviour disturbance with diplopia (2), A history of glue sniffing was elicited in 14, but in the remainder toluene assay confirmed the diagnosis. Thirteen children recovered completely; five still had psychological impairment and personality change on discharge from hospital but were lost to follow-up, and one has a persistent cerebellar ataxia one year after the acute episode, despite absence of further exposure. Toluene inhalation is an important cause of encephalopathy in children and may lead to permanent neurological damage. Diagnosis is most important if further damage due to continued abuse is to be prevented, and toluene assay is a valuable aid to diagnosis.